Life history traits of freshwater fish population and implications on aquatic biodiversity conservation: a review - SARKAR, U K; LAKRA, W S (The Indian Journal of Animal Sciences, 2010)
Knowledge on life history traits of fish and habitat requirements are very important in implementation of fishery management programmes, domestication of species under captive conditions, stock identification, population dynamics, development of captive breeding technology, assessment of conservation status, utilization of fishes as biological control, in situ and ex situ conservation. Life history characteristics of fish, including maximum size, growth rate, size at maturity, fecundity and migratory behaviour, have important implications for populations as well as their risk of extinction. Though phenotypic differences in life history parameters do not provide direct evidence of genetic isolation between stocks, but can indicate the prolonged separation of fish and also provide a firm basis for separate management units. The variation in life history traits of fish indicate phenotypic plasticity of the species which could be an important adoption trait, allowing them to respond to ecologically/habitat changes during their life time. Review of literature indicates that information on the life history parameters of most of the freshwater fishes from different lotic and lentic waters is rather fragmentary and understudied. The present paper reviews the relevance of the studies on life history traits of fish population and their implications in biodiversity conservation, synthesis of latest developments, knowledge gaps, research priorities and highlight important issues related to conservation and management of freshwater fishes